To shift a paradigm or not: worldviews at play in responsible management education literature. Issue 3 (2nd May 2022) - Stough, Talia; Ceulemans, Kim; Craps, Marc; Van Liedekerke, Luc; Cappuyns, Valérie
Abstract : Purpose: This study analyzes which worldviews on the interrelatedness of the economic, environmental and social systems are adopted in the literature on responsible management education (RME) and explores how this affects the way business schools educate future responsible managers. Design/methodology/approach: The sustainability-focused relational worldviews of Kurucz et al. (2014) were used to perform a content analysis on 100 articles from the field of RME to understand which worldviews are adopted and to distill potential implications of the prevalence of such worldviews in the RME field. Findings: In the sample, the most adopted view was the intertwined view that imagines a balance between the economic, environmental, and social system (61% of the articles). The subsuming worldview (highlighting the business case for sustainability) accounted for 8% of articles in the sample. The embedded worldview (a new paradigm that respects the limitations of the environmental and social systems) accounted for 31% of the articles in the sample. The disparate view (representing classic economic views of discrete systems) was not adopted, indicating a rather uniform belief that RME is about moving management education away from this view. Examining the evolution of views over the last 20 years, it can be observed that the embedded view is growing in popularity. The continuing prevalence of the ambiguous and malleable intertwined view in the RME literature could explain why so many RME initiatives have been taken in the last two decades, while simultaneously critics remain vocal that business schools are not preparing future managers to engage with ethics, responsibility, and sustainability (ERS). Originality/value: While sustainability-focused relational worldviews have been introduced in the RME literature, this study provides empirical evidence of the prevalence of such worldviews in the literature, allowing an exploration of the implications for the field. The presence of multiple — and at times competing — worldviews adds tension to the field of RME. Seen on the trajectory of increasingly progressive worldviews, the intertwined view is not limited by economic rationalism (like the subsuming view) but also stops short of requiring a full paradigm shift (like the embedded view).